Cultural threads in writing mastery: a structural analysis of perfectionism, learning self-efficacy, and motivation as mediated by self-reflection in chinese efl learners - Tao, Ye; Yu, Jianbin (BioMed Central, 2024)
Background: The study explores language acquisition in Chinese English as a Foreign Language (EFL) education, where English proficiency is crucial for global opportunities. As China gains prominence, the demand for English skills rises beyond communication to include academic and business success. The Chinese education system emphasizes proficient English writing for further education and professional achievement. This research investigates the complex linguistic context for EFL learners in China, analyzing the intersection of psychological factors, cultural nuances, varied pedagogy, and individual experiences. Methods: Structural Equation Modeling (SEM) is utilized for analysis, enabling the creation of a metric set to explore intangibles such as perfectionism, learning self-efficacy, motivation, study habits, cultural influences, and introspection. The research utilizes a diverse sample from multiple universities across different regions of China, incorporating demographic factors to encompass the varied characteristics within the EFL learner community. Results: Results reveal that perfectionism (β = 0.30, p < 0.001), learning self-efficacy (β = 0.25, p = 0.005), motivation (β = 0.35, p < 0.001), study habits (β = 0.20, p = 0.01), and self-reflection (β = 0.28, p < 0.001) significantly predict writing proficiency. Cultural effects (Beta = 0.15, p = 0.05) show a statistically significant, albeit minimal, impact. Mediation-moderation analysis underscores perfectionism as a mediator (Beta = 0.25, p = 0.005), emphasizing its influence on other predictors. Cultural factors act as moderators (Beta = 0.15, p = 0.01), shaping the link between predictors and writing skills. The combined mediation and moderation effects on writing proficiency are positively significant (Beta = 0.20, p = 0.02). Conclusions: This study makes a significant theoretical contribution, enhancing existing models and providing practical insights for EFL educators and policymakers. Emphasizing the intricate relationship between psychological factors and cultural dynamics underscores the necessity for a sophisticated, culturally sensitive approach to language acquisition in Chinese EFL instruction. Beyond language skills, the research recognizes the importance of fostering a conducive environment that encourages personal development, socio-cultural awareness, and a holistic learning approach.